New bisamide compounds from the bark of Aglaia eximia (Meliaceae). (September 2015) - Sianturi, Julinton; Purnamasari, Mayshah; Darwati,; Harneti, Desi; Mayanti, Tri; Supratman, Unang; Awang, Khalijah; Hayashi, Hideo
Graphical abstract: Two bisamide compounds, eximiamide A (1 ) and exiamiamide B (2 ) were isolated from the bark of Aglaia eximia (Meliaceae). Compounds1 and2 exhibited cytotoxicity activity against P-388 murine leukemia cells with IC50 values of 7.6 and 8.5 μg/mL, respectively. Highlights: Two new bisamides, exiamiamide A (1 ) and eximiamide B (2 ), were isolated from the bark of Aglaia eximia . Their structures were determined based on 1D, 2D NMR and MS data. Compounds1 and2 exhibited cytotoxic against P-388 murine leukimia cell lines. Abstract: Two new bisamide compounds, eximiamide A (1 ) and eximiamide B (2 ) were isolated from the bark of Aglaia eximia (Meliaceae). The chemical structures of the new compound were elucidated on the basis of spectroscopic data. All of the compounds were evaluated for their cytotoxic effects against P-388 murine leukemia cells. Compounds1 and2 exhibited cytotoxic activity against P-388 murine leukemia cells with IC50 values of 7.6 and 8.5 μg/mL, respectively.